Getting to 70%: Barriers to modern contraceptive use for women in Rwanda☆. (2nd August 2013) - Brunie, Aurélie; Tolley, Elizabeth E.; Ngabo, Fidèle; Wesson, Jennifer; Chen, Mario
Abstract: Objective: To identify reasons for non‐use of modern family planning in Rwanda, to examine specific barriers to contraception, and to explore psychosocial factors influencing modern contraceptive use. Methods: In total, 637 in‐union, parous, and non‐pregnant women aged 21–49 years participated in a cross‐sectional community‐based survey in 5 districts. In‐depth interviews (IDIs) were conducted with 54 women and 27 male partners. Multivariate logistic regression examined correlates of current non‐use. IDI transcripts were analyzed independently and compared thematically with survey findings. Results: Overall, 50% of survey respondents were using a modern method. Fertility‐ and partner‐related variables were key correlates of non‐use. The most commonly reported reasons for non‐use were related to perceived fecundity. Men were mostly supportive of contraceptive use and had an important role in a woman's decision to use contraception. Women's IDIs revealed misperceptions about fertility leading to gaps in contraceptive coverage, particularly postpartum. Those IDIs also highlighted how provider practices, including screening for pregnancy through direct observation of menses, may hamper contraceptive use. Conclusion: Programmatic recommendations include increasing information efforts aimed at men; developing effective messages about postpartum risk of pregnancy and training providers on postpartum contraceptive eligibility and needs; and reinforcing use of alternative pregnancy‐screening methods.